Detection and genetic characteristics of porcine circovirus type 2 and 3 in Henan province of China. (February 2022) - Jia, Yunfei; Zhu, Qianlei; Xu, Tong; Chen, Ximeng; Li, Hongxuan; Ma, Mengyao; Zhang, Yibei; He, Zejun; Chen, Hongying
Abstract: PCV2 is one of the most economically important viral agents in swine worldwide. Recently, PCV3 has been frequently reported, and the co-infection of PCV2 and PCV3 is common in China. In order to explore the distribution, epidemiology and genetic diversity of PCV2 and PCV3, a total of 1, 760 clinical tissue samples were randomly collected from 18 different regions in Henan province of China from October 2018 to September 2019 and screened for the presence of PCV2 and PCV3 by a duplex real-time PCR assay. The results showed that the positive rates of PCV2 and PCV3 were 72.90% and 5.17% respectively, and the co-infection rate of the two viruses was 3.64%. PCV2 and PCV3 are prevalent all year round. The prevalence of PCV2 in diseased pigs was 83.98%, higher than that in slaughterhouse pigs, while the prevalence of PCV3 in diseased pigs was 2.16%, slightly lower than that in slaughterhouse pigs. Furthermore, the complete genomes of 14 PCV2 and 3 PCV3 strains were obtained, among which 1 belonged to PCV2a, 5 belonged to PCV2b and 8 belonged to PCV2d. A new variant strain (XX2) might escape the host immune system. The phylogenetic analysis of PCV3 showed high nucleotide identity (>98%) between sequences obtained in this study and reference sequences. The results of this study might enrich the epidemiological data of PCV2 and PCV3 in Henan province and provide reference information for the comprehensive prevention and control of PCVAD. Highlights: The distribution, epidemiology and genetic diversity of PCV2/PCV3 were explored in Henan province. 1760 clinical samples were collected from 18 different regions from October 2018 to September 2019. The complete genomes of 14 PCV2 and 3 PCV3 strains were obtained.